CRISPR/Cas9 Technology Targeting Fas Gene Protects Mice From Concanavalin‐A Induced Fulminant Hepatic Failure - Liang, Wei‐Cheng; Liang, Pu‐Ping; Wong, Cheuk‐Wa; Ng, Tzi‐Bun; Huang, Jun‐Jiu; Zhang, Jin‐Fang; Waye, Mary Miu‐Yee; Fu, Wei‐Ming (Journal of cellular biochemistry, 2017)
ABSTRACT Fulminant hepatic failure is a life‐threatening disease which occurs in patients without preexisting liver disease. Nowadays, there is no ideal therapeutic tool in the treatment of fulminant hepatic failure. Recent studies suggested that a novel technology termed CRISPR/Cas9 may be a promising approach for the treatment of fulminant hepatic failure. In this project, we have designed single chimeric guide RNAs specifically targeting the genomic regions of mouse Fas gene. The in vitro and in vivo effects of sgRNAs on the production of Fas protein were examined in cultured mouse cells and in a hydrodynamic injection‐based mouse model, respectively. The in vivo delivery of CRISPR/Cas9 could maintain liver homeostasis and protect hepatocytes from Fas‐mediated cell apoptosis in the fulminant hepatic failure model. Our study indicates the clinical potential of developing the CRISPR/Cas9 system as a novel therapeutic strategy to rescue Concanavalin‐A‐induced fulminant hepatic failure in the mouse model. J. Cell. Biochem. 118: 530–536, 2017. © 2016 Wiley Periodicals, Inc. The in vivo delivery of CRISPR/Cas9 could maintain liver homeostasis and protect hepatocytes from Fas‐mediated cell apoptosis in the fulminant hepatic failure model. Our study indicates the clinical potential of developing the CRISPR/Cas9 system as a novel therapeutic strategy to rescue Concanavalin‐A‐induced fulminant hepatic failure in the mouse model.